Kajian Literatur Penerapan Perencanaan Pajak PPH Badan pada Perusahaan Baru Berdiri dalam Rangka Optimal Investasi - Mhd Hasymi (Yayasan Literasi Sains Indonesia, 2022)
In the current condition, taxes are the primary source of state income that contributes to the state budget compared to the source of income from foreign exchange for oil and gas and non-oil exports. Viewed from the side of the taxpayer, tax is a burden that is the company's main obligation to fulfill it in a timely manner. This study uses a literature review, where the results of qualitative writing will explain about tax planning at the beginning of the company theoretically. The author in making this research uses descriptive qualitative research methods. The research process includes the collectability of literature, laws, government regulations, and published journals, identification and analysis of research results related to tax planning at the start of the company, through Publish or Perish and Google Scholar. The results of the study are in the form of a conclusion that tax planning at the beginning of the company's establishment can optimize investment in a more productive direction for the completion of the company as a whole. Recommendations from the research are providing incentives (rewards) to taxpayers who report corporate tax returns supported by complete tax planning reports, minimizing or eliminating multiple interpretations of the implementation of tax regulations, issuing tax rules with a sense of justice and involving stakeholders from the Directorate General of Taxes.